Who Will They Turn to? The Perspectives of Middle School Girls Regarding Trustworthy Traits in Adults - Burcu Ozturk; Christina R. Miller; David A. McLeod; David Dickerson (Middle Grades Review, 2023)
Early adolescence is a time marked by upheaval and change. Youth are navigating increased social pressures from constant connection with peers. Youth have access to 24 hours of social connection via technology, but they increasingly report feelings of isolation, anxiety, and depression (Keles et al., 2020). They are also entering a world with increased political division, climate disasters, and decreases in public safety from events like mass shootings (Coronese et al., 2019; Follman et al., 2022). As youth navigate these new challenges, adults are seeking ways to understand better how to build meaningful connections with youth that may help mitigate the negative impacts of environmental and social stress. The potential for positive effects from adult/youth relationships is high, and even more important for girls, with research suggesting them to be at even higher levels of risk (Stallard et al., 2013). This paper explores adolescent girls' perspectives regarding who they identify as trustworthy adults and what traits make that person trustworthy. This exploration can build a foundation for fostering healthy relationships between both groups.
Keywords: Bullying; Suicidal ideation; Trustworthiness; Self-harm; Youth; Prevention